Curriculum Management for Strengthening Religious Moderation in Islamic Boarding Schools Al Mukmin - Doki Hermanto (PT. Islamic Research Publisher, 2023)
PPIM Ngruki has attracted controversy and is considered contrary to the New Order government since its establishment fifty years ago. This is because some of its founders rejected the establishment of the Single Principle of Pancasila as the State Ideology. Since then, the founders of PPIM Ngruki, including Abu Bakar Baásyir and Abdullah Sungkar, have been fugitives from the New Order government. Despite the fact that some PPIM Ngruki alumni are involved in such terror activities, people with links to the Al-Mukmin Ngruki pesantren are often considered members of the same group. Literature research or literature study uses a qualitative approach to obtain data and uses various literature as sources. In this study, researchers use the results of previous research on the subject or type of research related to the research subject. The instillation of tolerance values in the curriculum, teachers, and students shows the strengthening of religious moderation education. The cultivation of PPIM Ngruki's tolerance value is also seen from two things: first, PPIM Ngruki does not impose the enforcement of Islamic law; second, PPIM Ngruki received positive responses and had a middle stance on politics. Thus, it can be concluded that the cultivation and implementation of tolerance values in religious moderation education at PPIM Ngruki has gone well.